Therapeutic Targeting of Low-density lipoprotein receptor-related protein-1 (LRP1) gene in Ovarian Cancer: A Comprehensive Review - Krishna, R.B. Devi; Krishnamurthy, Nandini; Murali, Sanjana; Agarwal, Preet; Chellappan, Elizabeth Rani; Joseph, Leena Dennis; Keerthana, Banu; Francis, Andrea Mary (Journal of Medical Science, 2025)
Low-density lipoprotein receptor-related protein 1 (LRP1, also known as CD91) is a multifunctional endocytic and cell-signalling receptor widely expressed in various cell types, including neurons, fibroblasts, hepatocytes, muscle cells, astrocytes, and tumour cells. It maintains cellular homeostasis by mediating interactions with extracellular matrix proteins, growth factors, and proteases. These interactions enable LRP1 to act as a co-receptor that modulates and influences signalling pathways associated with cell migration, survival, and proliferation. In ovarian cancer, LRP1 is frequently activated and contributes to tumour progression. Functional studies have demonstrated that LRP1 promotes these malignant traits through activation of PI3K/Akt and MAPK/ERK pathways, while its inhibition suppresses proliferation and invasion. This review aims to comprehensively examine the functional role of LRP1 in ovarian cancer, with particular emphasis on its capacity to regulate tumour cell migration and invasion through key molecular pathways. Understanding these mechanisms may provide insights into novel therapeutic strategies for ovarian cancer treatment.